The Effect of Planning Regular Walking as Rehabilitation in Chronic Obstructive Pulmonary Patients Clinical Status - Robabeh Me'marian; Iesaa Mohammadi; Neda Mirbagheri (Journal of Rehabilitation, 2009)
Objective: Chronic obstructive pulmonary disease (COPD) is characterized with air flow restriction that this limitation is not refundable completely. This study is carried out in order to determine the effect of regular walking as rehabilitation plan on clinical status of chronic obstructive pulmonary disease (COPD) patients with moderate severity of disease. Materials & Methods: In this quasi experimental study 100 patients were selected simply from convenient samples of Isfahan hospitals and finally were assigned into two groups as control group (n=30)and experimental group (n=50).Data collection tools include Demographic data questionnaire and observation checklist of clinical status for measuring respiratory status and self report questionnaire about walking doing. All of tools complited in 3 stages: before intervention, end four week and two month after intervention. Data were analyzed by repeated measurement ANOVA, Paired T test and Independent T test. Results: There was no significant difference in mean score of dyspnea (P=0.1), sputum quality (P=0.45), respiration pattern (P=0.06) and lung auscultation (P=0.06) of control group at different stages of research, but in experimental group, these variants were significant (P-values were 0.01, <0.001, 0.004 and 0.03). Conclusion: Regular walking as rehabilitation plan in moderate chronic obstructive pulmonary disease patients improves clinical status of them (decrease of cough and sputum and regular respiration pattern and lung auscultation) and pulmonary function.